Relationship of muscle cramps to quality of life and sleep disturbance in patients with chronic liver diseases: A nationwide study. (30th May 2018) - Iwasa, Motoh; Karino, Yoshiyasu; Kawaguchi, Takumi; Nakanishi, Hiroyuki; Miyaaki, Hisamitsu; Shiraki, Makoto; Nakajima, Tomoaki; Sawada, Yasuhiko; Yoshiji, Hitoshi; Okita, Kiwamu; Koike, Kazuhiko
Abstract: Background & Aims: Although muscle cramps frequently occur in patients with cirrhosis, the importance of muscle cramps remains unclear. The aims of this study were to investigate the relationship of muscle cramps with quality of life (QOL) and sleep disturbance. In addition, this multi‐institutional collaborative study in Japan investigated factors associated with muscle cramps in patients with cirrhosis. Methods: A total of 1788 patients with chronic liver diseases including both non‐cirrhosis and cirrhosis completed a questionnaire survey investigating: (i) frequency of muscle cramps, (ii) relationship of muscle cramps to poor QOL and sleep disturbance, (iii) characteristics of patients who require therapeutic intervention and (iv) characteristics of patients prone to experiencing muscle cramps. Results: This study revealed that 51.8% of patients with cirrhosis have experienced muscle cramps. People who experienced muscle cramps were more likely to have reduced QOL and sleep disturbance if muscle cramps had (i) high frequency (occurring daily to a few times per week, P  < .01); (ii) long duration (between a few minutes and a few hours, P  < .01) and (iii) intense severity (visual analogue scale ≥4, P  < .01). Age, female sex, positive results for hepatitis C virus, low serum albumin concentration, and cirrhosis were independent factors related to the severity of muscle cramps. Conclusion: Muscle cramps occurred with great frequency and were associated with various factors such as age, sex, hepatitis C virus and liver function. Many patients experience poor QOL (26.3%) due to muscle cramps, and therapeutic interventions are therefore needed.